2021
DOI: 10.3390/su13115774
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Tourists: Responsible Behavior Triggered by the COVID-19 Pandemic

Abstract: Responsible tourism implies that all actors involved in tourism take responsibility for their actions. The concept of responsible tourism has been extensively addressed in tourism research and practice. However, studies analyzing the tourists’ contribution to responsible tourism have been neglected. Considering that tourists have the potential to contribute to economic, environmental socio-cultural, and institutional sustainability, this study focuses on the role tourists can play in responsible tourism. It al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 56 publications
(141 reference statements)
2
43
1
3
Order By: Relevance
“…Another study [43] found that the Chinese also did not want to travel to rural areas because of COVID-19 due to the perceived health hazard. Furthermore, in European countries such as Germany, Austria or Switzerland, the COVID-19 pandemic had significant impact on travel risk perception and the willingness to change or cancel travel plans [44,45]. On the other hand, Orindaru et al [46] showed that the pandemic and the decline in foreign travels had a positive effect on domestic tourism, including the use of rural tourism facilities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study [43] found that the Chinese also did not want to travel to rural areas because of COVID-19 due to the perceived health hazard. Furthermore, in European countries such as Germany, Austria or Switzerland, the COVID-19 pandemic had significant impact on travel risk perception and the willingness to change or cancel travel plans [44,45]. On the other hand, Orindaru et al [46] showed that the pandemic and the decline in foreign travels had a positive effect on domestic tourism, including the use of rural tourism facilities.…”
mentioning
confidence: 99%
“…Leisure travels to rural areas (agritourism, rural tourism, ecotourism), as indicated by Orindaru et al [45], are becoming increasingly attractive. Thus far, the attractiveness of this form of recreation has been based on qualities such as peace and quiet, contact with nature and relatively low prices [90,91].…”
mentioning
confidence: 99%
“…The eruption of COVID-19 has widely affected the sustainability of the tourism industry and has had wide-ranging impacts on destinations [35,36], bringing global tourism activities to a halt [37]. The occurrence of crises has unprecedentedly transformed the reality of tourist destinations worldwide by producing an unusual scenario of undertourism [5,[38][39][40].…”
Section: Covid-19 and The Responses Of The Tourism Industrymentioning
confidence: 99%
“…Certainly, these research prospects are under development. In a recently published paper related to the tourists' behavior during the pandemic, Eichelberger et al [63] established a qualitative study with potential tourists to assess their prospect of travelling during the pandemic and found that their responses showcased an "adaptation of travel habits, destination choices, travel patterns, and tourist awareness". In another paper addressing residents' insights, Joo et al [24] explored the perceived risks of residents in supporting tourism during the pandemic through indirect effects.…”
Section: Impact Of the Covid-19 Pandemic On Residents' Support For Sustainable Tourism Developmentmentioning
confidence: 99%
“…However, this tool has been under threat due to the current COVID-19 pandemic that took over the world, leaving tourism-dependent countries in strenuous economic situations. In this difficult circumstance, Eichelberger et al [63] argue that COVID-19 might provide the opportunity "to rethink travel behavior and thus incorporate more sustainability" in this industry. This pandemic and the international crisis have highlighted the important role of residents as key stakeholders in tourism [41,73].…”
Section: Theoretical Contributionsmentioning
confidence: 99%